Who will treat older patients? Should medical education focus more on activities aimed at displaying positive attitudes toward older people? The prevalence of ageism among students of medical and health sciences - Podhorecka, Marta; Husejko, Jakub; Woźniewicz, Agnieszka; Pyszora, Anna; Kȩdziora-Kornatowska, Kornelia (Frontiers in Public Health, 2022)
In the conditions of an aging society, a justification is found to explain the issue of the attitude of future health care workers, who are to care for elderly people in the future, toward these people, which will make it possible to predict in advance what problems related to the care of seniors may soon arise. After clarifying this issue, it will be important to distinguish the individual factors influencing this attitude in order to determine which social phenomena will require special attention. Eight hundred and three medical and health sciences students participated in the research from various fields of medical studies. A Survgo system was used, where an online questionnaire was placed and then posted in social media. Only students of medicine and healthcare facilities participated in the study. The first questionnaire contained socio-demographic questions. Then, the KOAP questionnaire and Welch's t-test were used, and finally the proprietary questionnaire on contact with seniors. Analyses were conducted using the R Statistical language. Scores on the KAOP questionnaire ranged from 122.4 to 134.57. The highest scores were shown for physiotherapy students and the lowest for pharmacy students. The highest level of attitude toward elderly was reported in students of 1st to 3rd year of study. For 4th-5th year or supplementary level students, attitude levels were decreasing. Welch's t-test showed that the level of attitude toward old people in men was significantly higher than in women. There was no significant correlation between the age factor on the quotient scale and the KOAP score. Married individuals had significantly higher KAOP scores compared to singles and those in an informal relationship. No significant differences between the study stage factor and KAOP score have been found. Those who live and/or have regular contact with the elderly were characterized by higher KAOP questionnaire scores. The attitude toward the elderly depends on many factors, such as the chosen field of study, stage of education, contact with the elderly, gender or marital status. In order to develop proper contact with seniors, the solution may be to influence modifiable factors, especially the correct education of future health care workers.